2019
DOI: 10.1002/cctc.201901457
|View full text |Cite
|
Sign up to set email alerts
|

Oscillation of Work Function during Reducible Metal Oxide Catalysis and Correlation with the Activity Property

Abstract: Deducing from the fact that RMO catalysis typically involves reversible valence states transformation of active sites, we report one new model that uses RMO work function and its oscillation as descriptors to depict the activity property. Our experiments and DFT simulations of CO oxidation model reaction lead to an inverted volcano correlation between the two descriptors and the activity energy barrier, which shows good consistence with this new model and thus validates its effectiveness. The findings of work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…They discovered that the RMO activity can be depicted by two governing parameters: the work function and the work function oscillation of catalyst materials. 41 The reducibility of RMO and the corresponding activity property in CO oxidation can be regulated by substitution or incorporation with other cations. 42 For example, the study of dopants-modified TiO 2 found a boost in activity in CO oxidation, while in situ Fourier-transform infrared spectroscopy (FT-IR) and X-ray photoelectron spectroscopy (XPS) characterizations confirmed that the crystal phase of the oxides has an impact on the catalytic performance.…”
Section: Rmo Catalysts In Co Conversionmentioning
confidence: 99%
See 1 more Smart Citation
“…They discovered that the RMO activity can be depicted by two governing parameters: the work function and the work function oscillation of catalyst materials. 41 The reducibility of RMO and the corresponding activity property in CO oxidation can be regulated by substitution or incorporation with other cations. 42 For example, the study of dopants-modified TiO 2 found a boost in activity in CO oxidation, while in situ Fourier-transform infrared spectroscopy (FT-IR) and X-ray photoelectron spectroscopy (XPS) characterizations confirmed that the crystal phase of the oxides has an impact on the catalytic performance.…”
Section: Rmo Catalysts In Co Conversionmentioning
confidence: 99%
“…12). 41 This model considered the oscillation of active sites between different oxidation states and suggested that the material parameters associated with both states collectively control the activity property. To a certain extent, the used Δ H F and Δ E vac material properties and their correlation with the reaction properties in previous studies already reveal the importance of both active site states during RMO catalysis.…”
Section: Outlook and Perspectivementioning
confidence: 99%
“…Arguably, materials with a lower work function that operate at a lower temperature are noted to release more electrons [29] , [30] . Consequently, the work function is of tremendous technological importance in many applications such as thermionic energy converters [31] , [32] , printed and organic electronics [42] , [43] , [44] , emerging perovskite solar cells technology fluorescent light tube [45] , electron emission gadgets (terahertz sources) [46] , [47] , scientific instruments that use electron sources [30] , [39] , [40] , [41] , catalysis [42] , [43] , [50] , [51] , electrochemistry [52] , [53] , [54] , corrosion resistance [25] , [55] , [56] and as an interfacial diagnostic tool in material [57] . These novel applications are realizable if the materials are mechanically, chemically and thermally stable (thoriated tungsten and lanthanum hexaboride), preferably caesiated metals of low work function [48] , [49] , [58] , [59] , as applied in thermionic energy converter [38] , [60] , [61] , [62] , [63] .…”
Section: Introductionmentioning
confidence: 99%